Interview with Kurt Goldberger - Hádková, Jana (Iluminace, 1991)
An interview with Kurt Goldberg, a director of scientific, popular science and documentary films who emigrated twice (1948 and 1968) and settled in Munich.
Keywords: Kurt Goldberger; Czech documentary film; Czech film exile